Medical countermeasures after a radiological event: An update from the CATO project. (November 2014) - Leiterer, Alexandra; Bardot, Isabelle; Ménétrier, Florence; Bardot, Sébastien; Grémy, Olivier; Bérard, Philippe; Pech, Annick; Favaro, Pascal
Abstract Purpose: As part of the European project 'CBRN crisis management: Architecture, Technologies and Operational Procedures' (CATO), an open Toolbox is in development that will address the needs of all stakeholders from first responders to decision makers. A database on chemical, biological, radiological and nuclear (CBRN) threats, including information on medical countermeasures, will be integrated in this Toolbox. Results and conclusions: After a radiological accident, review of national and international recommendations for the major countermeasures (stable iodine, Prussian Blue, and diethylenetriaminepentaacetic acid [DTPA]) showed that discrepancies in treatment protocols and open questions remain: How to proceed in case of repeated release of radioiodines? Which dosage for Prussian Blue? For which radionuclides is DTPA really effective? This paper brings elements to answer these questions.